Pros and Cons of Adopting Artificial Diet for Silkworms - Ramya Harika K; Karthick Mani Bharathi B.; Susikaran S; Kiruthika C; Vasanth V (International Journal of Insects, 2024)
Silkworms (Bombyx mori L.) were renowned for their ability to produce silk fibers and have played an essential role in the textile industry for thousands of years. Traditionally, these insects have been raised on mulberry leaves which provide them with the necessary nutrients to grow and spin silk. However, in recent years, advancements in agricultural and industrial practices have led to the development of artificial diets for silkworms. These synthetic diets are designed to simulate the nutrients found in mulberry leaves thus providing a potentially more efficient and scalable solution for sericulture. The shift towards artificial diets has sparked significant debate among researchers, sericulturists, and farmers, as they weigh the potential advantages and disadvantages. This article explores the pros and cons of adopting artificial diets for silkworms thus analyzing the impact on silkworm growth, silk production, and the broader sericulture industry. By examining these factors, we can better understand whether artificial diets can become a viable alternative to traditional mulberry feeding methods.
Keywords: Artificial diets; cocoon quality assessment; mulberry leaf alternatives; production efficiency; sericulture innovation; silkworm rearing